GROSS OPERATING PROFIT (GOP) ACHIEVEMENT POSITIVE STRATEGY IN THE NEW NORMAL ERA (Case Study at Swiss Belresidences Hotel Kalibata Jakarta): Case Study at Swiss Belresidences Hotel Kalibata Jakarta - Dede Fahruroji (Universitas Islam Lamongan, 2023)
The COVID-19 pandemic has impacted various sectors of life, including the hotel business. Due to restrictions on community mobility resulting in a decrease in room occupancy rates, MICE (Meeting, Incentive, Convention, and Exhibition), and the provision of social events at the Swiss Belresidence Hotel Kalibata Jakarta. This decrease can have an impact on decreasing hotel revenues which can affect the acquisition of Gross Operating Profit (GOP) which is calculated by revenue minus costs and expenses that must still be paid. This study aims to analyze the achievement of Gross Operating Profit (GOP) during the pandemic and predict it for the next 5 years, as well as formulate a strategy so that the GOP obtained is in accordance with the target. The data in this study were obtained by SWOT analysis through observation, interviews and documentation. Informants in this study are financial statements and hotel management. The data analysis technique in this study used qualitative descriptive. The results of this study are strategies that can be formulated for Swiss-Belresidences Kalibata Hotel, such as implementing a strategy of utilizing green areas in the hotel, offering attractive promos with complete facilities and easy transportation access. So the GOP for 2021 and predictions for the next 5 years GOP obtained are positive with an average growth of around 11.39 percent.